KEMAMPUAN MENULIS KEMBALI ISI CERPEN “SEPOTONG BURGER” KARYA SANICE ALFIETA OLEH SISWA KELAS IX SMP N I SEI KANAN LABUHAN BATU SELATAN TAHUN PEMBELAJARAN 2012/2013 - Junaina Umairi (JURNAL SASTRA INDONESIA (SASINDO), 2014)
Writing is a very important skill in life, are notonly important in education, but also very important inpeople's lives. As soon as re-write the contents of theshort story, students should be able to understand the wayof story is written by the author, from the beginning tounderstand the intrinsic elements and understand themeaning of difficult words contained in a short story. Theability of the students' understanding after reading theshort story can be known by asking students to retell orrewrite the content of the short stories that have been readby using their own language.Keywords, Writing, Short Story